2021
DOI: 10.1002/pol.20210066
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of polyurethane wastes using different carboxylic acids via acidolysis to produce wood adhesives

Abstract: This study aims to provide further understanding on the depolymerization of polyurethanes (PU) via acidolysis. Therefore, polyurethane foams scraps are chemical recycled using different dicarboxylic acids, namely succinic and phthalic dicarboxylic acids, being the reaction products identified using Fourier‐transform infrared spectroscopy, nuclear magnetic resonance and gel permeation chromatography. The results obtained show that succinic acid has higher efficiency as cleavage agent, as a result, the succinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 36 publications
(53 reference statements)
1
35
0
Order By: Relevance
“…Recently, acidolysis of flexible PUF waste (a mixture of different PUF types) with diacids (PUF/diacid weight ratio of 4.5–5.5) in bulk under an inert atmosphere by conventional heating was reported. 26 28 After 5 h, the resulting viscous polyol was discharged from the reactor and reused without any purification as a partial substitute (up to 30 wt %) of the primary polyol for the production of new rigid and flexible foams 26 , 27 as well as polyurethane adhesives and coatings for wood. 28 , 29 It is reported that the stiffness of the flexible PUFs increases with an increasing RP content, which was attributed to the presence of aromatic components in the RP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, acidolysis of flexible PUF waste (a mixture of different PUF types) with diacids (PUF/diacid weight ratio of 4.5–5.5) in bulk under an inert atmosphere by conventional heating was reported. 26 28 After 5 h, the resulting viscous polyol was discharged from the reactor and reused without any purification as a partial substitute (up to 30 wt %) of the primary polyol for the production of new rigid and flexible foams 26 , 27 as well as polyurethane adhesives and coatings for wood. 28 , 29 It is reported that the stiffness of the flexible PUFs increases with an increasing RP content, which was attributed to the presence of aromatic components in the RP.…”
Section: Introductionmentioning
confidence: 99%
“…Several recycling technologies have been developed with different mechanisms of urethane bond degradation. Glycolysis and acidolysis , have been successfully used at the industrial scale, hydrolysis , has been introduced at the pilot scale, while aminolysis and phosphorolysis have been developed only at the laboratory scale. Chemical recycling of PUFs is carried out at high temperatures, mainly by conventional heating, although there are some reports on microwave (MW)-assisted degradation processes, especially in the case of glycolysis, where MW heating shortens the reaction time and improves the reaction yield. , Theoretically, all recycling technologies for polyether-based PUFs lead to hydroxyl-functionalized polyether polyol and oligourea hard segments end-capped with the applied degradation reagent. ,, Unfortunately, the existing methods of chemical recycling of PUFs mainly suffer from incomplete and/or nonselective degradation of urethane linkages, as partial cleavage of urea groups in the hard segments also occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Both saturated and unsaturated dicarboxylic acids were investigated as acidolysis reagents. The research group from the University of Aveiro (Portugal) had a particularly remarkable contribution in this topic, succinic acid being identified as the most valuable reagent for the acidolysis process [ 10 , 11 , 12 ]. Rigid polyurethane foams were produced at laboratory scale using up to 30% of this recycled polyol [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This impact is so sever, that hundreds of marine species have been reported to be affected by it 1 . Due to these concerns, petroleum‐based products/objects are starting to be produced using renewable feedstocks or other residues, based on the circular economy concept 2–11 . One example is the coffee cups used in the vending machines.…”
Section: Introductionmentioning
confidence: 99%